Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Microseismic monitoring of columnar jointed basalt fracture activity: a trial at the Baihetan Hydropower Station, China - Bing-Rui Chen; Qing-Peng Li; Xia-Ting Feng; Ya-Xun Xiao; Guang-Liang Feng; Lian-Xing Hu (Journal of Seismology, 2014)

DNA Methylation: Roles in Rheumatoid Arthritis - Feng-Lai Yuan; Xia Li; Rui-Sheng Xu; Dong-Lin Jiang; Xiao-Gang Zhou (Cell Biochemistry and Biophysics, 2014)

Distinctive expression and cellular distribution of dopamine receptors in the pancreatic islets of rats - Ye Chen; Feng Hong; Hui Chen; Rui-Fang Fan; Xiao-Li Zhang; Yue Zhang; Jin-Xia Zhu (Cell and Tissue Research, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Expression of bone morphogenetic protein 2, 4, and related components of the BMP signaling pathway in the mouse uterus during the estrous cycle - Yan Li; Quan-wei Wei; Jian-gang Feng; Mu-lin Xu; Rui-hua Huang; Fang-xiong Shi (Journal of Zhejiang University-SCIENCE B, 2014)

Identification of a putative cognate sensor kinase for the two‐component response regulator HrpG , a key regulator controlling the expression of the hrp genes in X anthomonas campestris pv. campestris - Rui‐Fang Li; Guang‐Tao Lu; Lei Li; Hui‐Zhao Su; Guo‐fang Feng; Ya Chen; Yong‐Qiang He; Bo‐Le Jiang; Dong‐Jie Tang; Ji‐Liang Tang (Environmental Microbiology, 2014)
Summary The bacterial phytopathogen X anthomonas campestris pv. campestris ( Xcc ) relies on the hrp (hypersensitive response and pathogenicity) genes to cause disease and induce hypersensitive response ( HR ). The hrp genes of bacterial phytopathogens are divided into two groups. Xcc hrp genes belong to group II . It has long been known that the group II hrp genes are activated by an AraC ‐type transcriptional regulator whose expression is controlled by a two‐component system ( TCS ) response regulator (named HrpG in Xcc ). However, no cognate sensor kinase has yet been identified. Here, we present evidence showing that the Xcc open‐reading frame XC _3670 encodes a TCS sensor kinase (named HpaS ). Mutation of hpaS almost completely abolished the HR induction and virulence. Bacterial two‐hybrid and protein pull‐down assays revealed that HpaS physically interacted with HrpG . Phos‐tag™ SDS‐PAGE analysis showed that mutation in hpaS reduced markedly the phosphorylation of HrpG in vivo . These data suggest that HpaS and HrpG are most likely to form a TCS . We also showed that XC _3669 (named hpaR2 ), which is adjacent to hpaS and encodes a putative TCS response regulator, is required for full virulence but not HR induction. HpaR2 also physically interacted with HpaS , suggesting that HpaS may also form another TCS with HpaR2 .

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

An automatic seismic signal detection method based on fourth-order statistics and applications - Xi-Qiang Liu; Yin Cai; Rui Zhao; Yin-Gang Zhao; Bao-An Qu; Zhi-Jun Feng; Hong Li (Applied Geophysics, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Roseomonas alkaliterrae sp. nov., isolated from an alkali geothermal soil sample in Tengchong, Yunnan, south-west China - Lei Dong; Hong Ming; Yi-Rui Yin; Yan-Yan Duan; En-Min Zhou; Guo-Xing Nie; Hui-Geng Feng; Lan Liu; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Zhizhongheella caldifontis gen. nov., sp. nov., a novel member of the family Comamonadaceae - Lei Dong; Hong Ming; Lan Liu; En-Min Zhou; Yi-Rui Yin; Yan-Yan Duan; Guo-Xing Nie; Hui-Geng Feng; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

Molecular dynamics-based self-organizing molecular field analysis on 3-amino-6-arylpyrazines as the ataxia telangiectasia mutated and Rad3 related (ATR) protein kinase inhibitors - Hao Luo; Jianyou Shi; Lufei Lu; Feng Wu; Meng Zhou; Xueyan Hou; Wenjuan Zhang; Zhengyu Ding; Rui Li (Medicinal Chemistry Research, 2014)

Converting natural vegetation to farmland alters functional structure of ground-dwelling beetles and spiders in a desert oasis - Feng-Rui Li; Ji-Liang Liu; Te-Sheng Sun; Bo-Wen Jin; Li-Juan Chen (Journal of Insect Conservation, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)